Correlation between antioxidant and anticancer activity and phenolic profile of new Apulian table grape genotypes (V. Vinifera L.) - Milella, Rosa Anna; De Rosso, Mirko; Gasparro, Marica; Gigante, Isabella; Debiase, Giambattista; Forleo, Lucia Rosaria; Marsico, Antonio Domenico; Perniola, Rocco; Tutino, Valeria; Notarnicola, Maria; Velasco, Riccardo; Flamini, Riccardo (Frontiers in Plant Science, 2023)
Grapes represent a significant source of phenolic compounds known for their health-promoting properties, such as antioxidant capacity on normal cells and prooxidant activity on tumor cells. The genotype highly affects the polyphenolic composition in grapes and, consequently, the nutritional quality of berries. This work aimed to characterize the phenolic composition, the antioxidant, and anticancer activity of grape skin extracts (GSEs) of nine new table grape genotypes selected from a breeding program to obtain new cultivars of seedless table grapes, well adapted to the climatic change and with higher nutraceutical properties. The relationship between the grape polyphenolic profile, characterized by Ultra-High-Performance Liquid Chromatography/Quadrupole-Time of Flight mass spectrometry analysis, and the antioxidant and anticancer activity of GSE, was investigated. GSE antioxidant activity was determined by the ABTS, DPPH, and ORAC assays; GSE cell growth inhibition test was carried out in the Caco2 human cancer cell line. The nine GSEs showed different flavonoid and non-flavonoid profiles, and all possessed antioxidant activity, with the ‘Aika N.’, ‘Turese N.’, and ‘Egnatia N.’ the most active. As anticancer activity against the tested cancer cell line, ‘Daunia N.’ and ‘Apenestae N.’ showed the EC50 after 24 h of 35.60 µg/mL and 150.91 µg/mL, respectively. Interestingly, among the different classes of polyphenolics, flavan-3-ols e proanthocyanidins showed the highest positive correlation with the anticancer activity of extracts. These findings can be helpful for the preparation of new extracts for the pharmaceutical and nutraceutical industry and geneticists working in vine breeding programs.